Hemiplejia, afasia, neuroplasticidad y arteterapia - Albillo, Merche (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2007)
There is substantial scientific support for the effectiveness of neuroplasticity as a resource that our cerebrum uses to palliate the effects of a brain injury. Once we have this knowledge, the next step is to make it useful in a real way,to all those persons that have suffered some kind of brain accident. The therapeutic reality that we find on the books is, still, far away from the therapeutic reality that we meet on the street.The steps that we´ll take,as therapists,in our every day work, will approach both realities in the way that we are able to facilitate people the necessary means they need to work for their own health. The public health system has limited economic resources so, it becomes necesary to think over costs and profits in order to establish therapeutic priorities; this fact dehumanizes the personal tragedies that ill persons and their families are living. In the other hand, the way that the geriatric institutions deal with elder and aged persons and the treatment that they receive, deserves a deep reflection. We should think over what we are doing to our elders.Is it ethic to profit thanks to the miseries and the needs of aged persons, without making anything but a good marketing to dignify their living? To know neuroplasticity as an endogenous resource that our cerebrum brings us to palliate the effects of brain damage; to approach to the mechanisms that make it possible and to know the tools, that we, as therapists, have in order to activate them, are both important cuestions to make effective our work with aphasic or plegia affected persons. It is important trying to see how, the smallest external stimulus is looking for a way, many times plenty of obstacles, to our brain and then, when he gets there, he tries to get out again as an action through routes that many times are broken. Our duty as Artherapists is to help him to find alternative ones, just in case that restoring the original ones became imposible. Bebo, my friend show me this.
Keywords: Neuroplasticity; Aphasic; Plexia; Hemiplejia